Fluid Mechanics Theory and Applications - Muhammad Noor Afiq Witri Muhammad Yazid,; Ummikalsom Abidin,; Fazila Mohd Zawawi,; Mohamad Nur Hidayat Mat,; Zulhanafi Paiman, (2024)
Fluid mechanics is a fundamental branch of physics and engineering that plays a crucial role in various industries. Understanding the behavior of fluids is essential for the design and operation of countless system and technologies; from the efficient transport of water through pipelines to the aerodynamics that propel aircraft through the skies.It is with great pleasure that we introduce “Fluid Mechanics: Theory and Applications,” a comprehensive textbook writen to provide you with a deep understanding of the fascinating world of fluid mechanics. With this textbook, our aim is to bridge tha gap between theory and practical applications, making this complex subject accessible and engaging. In addition, this book has been born out of a desire to offer a valuable resource to students, researchers and professionals seeking to master the principles of fluid mechanics.This book is based on experience in teaching and researching fluid mechanics by the authors in the past at Faculty of Mechanical Engineering, Universiti Teknologi Malaysia (UTM) as well as other institute of higher learning. Our passion for this subject have driven us to find innovative ways to convey its concepts to learners. This book is the culmination of that journey, and we hope it serve as your guiding light.